The Influence of Employee Engagement and Self-efficacy on the Performance of PDAM Tirtauli Pematangsiantar Employees - Pricila Natalia Sembiring; Onan Marakali Siregar (Formosa Journal of Applied Sciences, 2023)
This research aims to determine the influence of Employee Engagement and Self-efficacy on employee performance at PDAM Tirtauli Pematangsiantar. This research uses quantitative methods involving 74 employees as research samples. The sampling technique is Simple Random Sampling. The data collection used was a questionnaire using a Likert scale which was distributed to respondents directly. The data analysis technique uses instrument validity and reliability testing, classical assumption testing and hypothesis testing using multiple linear regression analysis assisted by SPSS. The results of this research show that employee engagement and self-efficacy variables have a positive and significant effect on employee performance partially and simultaneously. The coefficient of determination test shows that there is a fairly close relationship between employee engagement and self-efficacy on employee performance with an R value of 0.661.